Glass shards masquerading as calcifications in the breast: A case report - Akriti Khanna, MD; Margot S. Peters, MD; Katrina N. Glazebrook, MB, ChB; Giang H. Nguyen, MD, DPhil; Caleb M. Tsetse, MB, ChB, MD; Tiffany M. Sae-Kho, MD (Radiology Case Reports, 2024)
Noniatrogenically acquired foreign bodies in the nipple-areola complex or breast skin are rare and can have variable imaging features, depending on the nature of the foreign material. We present the case of a 41-year-old female who had numerous apparent round and punctate calcifications in the right periareolar breast, predominantly within the skin. The biopsy showed multiple glass shards on a background of scar tissue. Further discussion with the patient confirmed that the glass shards were acquired during a motor vehicle accident several years earlier. We also review the types of foreign body material observed in the breast, the imaging appearance of glass foreign bodies in soft tissue, and methods of removal.